2018
DOI: 10.1007/s10803-018-3564-3
|View full text |Cite
|
Sign up to set email alerts
|

The Feeling of Me Feeling for You: Interoception, Alexithymia and Empathy in Autism

Abstract: Following recent evidence for a link between interoception, emotion and empathy, we investigated relationships between these factors in autism spectrum disorder (ASD). 26 adults with ASD and 26 healthy participants completed tasks measuring interoception, alexithymia and empathy. ASD participants with alexithymia demonstrated lower cognitive and affective empathy than ASD participants without alexithymia. ASD participants showed reduced interoceptive sensitivity (IS), and also reduced interoceptive awareness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
133
10
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 83 publications
(122 reference statements)
17
133
10
3
Order By: Relevance
“…A recent study revealed that impaired interoceptive awareness, but not interoceptive sensitivity, is linked to autistic traits, alexithymia, and empathy. 126 Other studies in nonautistic populations have demonstrated a link between high alexithymia and impairments in interoceptive accuracy. 127 Together, these results suggest that interoceptive accuracy may be impaired in autistic individuals, and that this may be particularly coupled with emotion-processing deficits.…”
Section: Autism Spectrum Conditionsmentioning
confidence: 97%
“…A recent study revealed that impaired interoceptive awareness, but not interoceptive sensitivity, is linked to autistic traits, alexithymia, and empathy. 126 Other studies in nonautistic populations have demonstrated a link between high alexithymia and impairments in interoceptive accuracy. 127 Together, these results suggest that interoceptive accuracy may be impaired in autistic individuals, and that this may be particularly coupled with emotion-processing deficits.…”
Section: Autism Spectrum Conditionsmentioning
confidence: 97%
“…Interoceptive dysregulation has been found in ASC (see DuBois et al 2016) with some intriguing links to oxytocin (Quattrocki and Friston 2014). However, since interoceptive dysregulation increases alexithymia-difficulty identifying one's own feelings and emotions-it has been argued that this underlies many of the social-emotional difficulties present in ASC (Mul et al 2018;Shah et al 2016). Specifically, it appears that lower interoception reduces emotional fidelity and thus could contribute to ASC through alexithymia.…”
Section: Influences Of Alexithymia and Interoceptionmentioning
confidence: 99%
“…Such impairment in the affective representation system would lead to an inability to form a consciously accessible representation of one’s own affective state, which is consistent with the diagnostic criterion of alexithymia as being aware of having an emotion, yet being unsure as to what emotion one experiences. In line with this, recent findings indicate that alexithymia is linked to a lack of interoceptive awareness (Mul et al, 2018), an important aspect of empathy, and that alexithymia may even be characterized by a general failure of interoception (Brewer et al, 2016; Murphy et al, 2018). However, interoceptive accuracy (a lower, physiological level of emotional awareness, which is often measured using heart beat counts) might be increased in individuals with high levels of alexithymia (Ernst et al, 2013; Scarpazza et al, 2017), in line with their tendency to overly focus on bodily signals.…”
Section: Introductionmentioning
confidence: 58%